Weber against Luhmann: for a heuristic of the (in) differentiation - Silva, Lucas Trindade da (FCL-UNESP Laboratório Editorial, 2021)
The basic element of Niklas Luhmann’s sociology is the definition of modernity by the primacy of functional differentiation, the last form of social differentiation preceded by segmentation, center/periphery and stratification. In a functionally differentiated world society, each (sub) system performs its autopoietic closure, based on communication, on its own and exclusive binary codes. Such conception of differentiation in modern society tends to an unproductive formalism when the operative intransitivity of binary codes, the opposition between differentiation and hierarchy, and the impossibility of thinking about processes of indifferentiation are carried to the ultimate consequences. Against such formalistic rigidity of the concept of functional differentiation in Luhmann, I argue that the classical enunciation of social spheres’ autonomization in the Intermediate Consideration – insofar as Weber at first thinks such a process from the possible affinities, tensions and even colonizations between the different spheres – offers a powerful and flexible (un) differentiation heuristic to think modern and contemporary society, freeing us from a set of impasses posed by the luhmannian concept of functional differentiation.